Anxiety-like behavior and altered hippocampal activity in a transgenic mouse model of Fabry disease - Kai Kummer; Jeiny Luna Choconta; Marie-Luise Edenhofer; Archana Bajpai; Gopuraja Dharmalingam; Theodora Kalpachidou; David A. Collier; Michaela Kress (Neurobiology of Disease)
Background: Fabry disease (FD) patients are known to be at high risk of developing neuropsychiatric symptoms such as anxiety, depression and cognitive deficits. Despite this, they are underdiagnosed and inadequately treated. It is unknown whether these symptoms arise from pathological glycosphingolipid deposits or from cerebrovascular abnormalities affecting neuronal functions in the central nervous system. We therefore aimed to fill this knowledge gap by exploring a transgenic FD mouse model with a combination of behavior, transcriptomic, functional and morphological assessments, with a particular focus on the hippocampus. Results: Male FD mice exhibited increased anxiety-like behavior in the open field test, accompanied by a reduced exploratory drive in the Barnes maze, which could be related to the increased deposition of globotriaosylceramide (Gb3) identified in the dentate gyrus (DG). Hippocampus single-cell sequencing further revealed that Gb3 accumulation was associated with differential gene expression in neuronal and non-neuronal cell populations with granule, excitatory and interneurons, as well as microglia and endothelial cells as the main clusters with the most dysregulated genes. Particularly FD hippocampal neurons showed decreased electrical baseline activity in the DG and increased activity in the CA3 region of acutely dissected hippocampal slices. Conclusions: Our study highlights transcriptional and functional alterations in non-neuronal and neuronal cell clusters in the hippocampus of FD mice, which are suggested to be causally related to anxiety-like behavior developing as a consequence of FD pathology in mouse models of the disease and in patients.